ANALISIS MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI PADA SISWA KELAS XII DARI KELUARGA NELAYAN - Nandasari, Wika; Bahari, Yohanes; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study entitled "Analysis of Interests Continuing Study to Higher Education in Class XII Students from Fishermen's Family in Senior High School 1 Pemangkat Academic Year 2018/2019". The purpose of this study was to find out (1) The interest in continuing to study in college in class XII students of the fishing family, (2) The factors that influence student interest, (3) The obstacles in taking study. This research was a qualitative research with a descriptive approach. Information is obtained through direct observation, interviews, and documentation. The data validity used was source, data and time tringulation. The results of this study indicate that: (1) The interest in continuing to study in college in class XII students from the fishing family is classified as high. (2) Factors that influence such as peers, family and school environment are good in supporting students, but in the community less motivating. (3) The obstacle to continue is the low income of parents and the environment around the residence that is less supportive.Â Â Keywords: Student Interest, Family of Fishermen, College.